A difference of squares is a binomial of the form:
a^{2} – b^{2}
Take note that the first term and the last term are both perfect squares.
When we factor a difference of two squares, we will get
a^{2} – b^{2} = (a + b)(a – b)
This is because (a + b)(a – b) = a^{2}– ab + ab – b^{2} = a^{2}– b^{2}
Example:  x^{2} – 25 = 0 
x^{2} – 5^{2} = 0  
(x + 5)(x – 5) = 0  
We get two values for x: 

Be careful! This method only works for difference of two squares and not for the sum
of two squares:
a^{2} + b^{2} ≠
(a + b)(a – b)
Example :
Factor
a) x^{2}– 9
b) 4x^{2}– 25
c) 2x^{2}– 32
d) πR^{2}– πr^{2}
Solution:
a) x^{2}– 9
= x^{2}– 3^{2}
= (x + 3)(x – 3)
b) 4x^{2}– 25
= (2x)^{2}– (5)^{2}
= (2x + 5)(2x – 5)
c) 2x^{2}– 32
= 2(x^{2}– 16)
= 2(x^{2} – 4^{2})
= 2(x + 4)(x – 4)
d) πR^{2}– πr^{2}
= π(R^{2}– r^{2})
= π(R + r)(R – r)
Rotate to landscape screen format on a mobile phone or small tablet to use the Mathway widget, a free math problem solver that answers your questions with stepbystep explanations.